2015
DOI: 10.1111/coa.12434
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in 794 patients with a peripheral facial palsy using the FaCE Scale: a retrospective cohort study

Abstract: While counselling patients on what to expect during the recovery process after facial paralysis is an important part of any clinical visit, FaCE score correlations suggest that female patients with chronic facial palsy and increased age constitute a patient category that may require additional time and attention to prevent or mitigate psychosocial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
97
1
6

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 34 publications
5
97
1
6
Order By: Relevance
“…The most commonly raised concerns centred on eye function, with 12 participants mentioning a total of 27 problems. This is not surprising as previous studies have shown a similar result . In our study, participants cited an inability to blink, excessive dryness, visual impairment and the need to tape their affected eye shut at night as major problems in their day‐to‐day life.…”
Section: Discussionsupporting
confidence: 83%
“…The most commonly raised concerns centred on eye function, with 12 participants mentioning a total of 27 problems. This is not surprising as previous studies have shown a similar result . In our study, participants cited an inability to blink, excessive dryness, visual impairment and the need to tape their affected eye shut at night as major problems in their day‐to‐day life.…”
Section: Discussionsupporting
confidence: 83%
“…There is relatively scant published information about FP disability as it relates to etiology. Most authors who studied it found that etiology was not a predicting factor of PROMs . One previous study compared the morbidity of facial nerve dysfunction arising from surgical intervention for VS (n = 53) with those resulting from Bell palsy (n = 22).…”
Section: Discussionmentioning
confidence: 99%
“…20,21,38,39 In 2 cross-sectional studies assessing QOL in patients with acoustic neuroma, Ryzenman et al 21 found that 28% of patients were significantly affected by facial weakness, and Lee et al 38 found a significantly lower QOL scores in patients with facial paralysis compared with normal patients. Looking at patients with all-cause facial paralysis at initial presentation, Kleiss et al 20 found that patients with facial paralysis have a mean (SD) baseline Facial Clinimetric Evaluation score of 47.3 (19.2) representing health-related QOL on a scale of 0 to 100. Our study expands on these findings by comparing QOL scores between patients with all-cause facial paralysis and control patients and presenting a model showing that QOL scores are significantly affected by facial paralysis.…”
Section: Discussionmentioning
confidence: 99%